2013
DOI: 10.1111/j.2042-7158.2012.01598.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory, antioxidative and matrix metalloproteinase inhibitory properties of 20(R)-ginsenoside Rh2 in cultured macrophages and keratinocytes

Abstract: 20(R)-Rh2, a minor stereoisomer of ginsenoside Rh2, possesses matrix metalloproteinase inhibitory, anti-inflammatory and antioxidative activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Except for ginsenoside Rg 3 , other stereoisomeric saponins have also been found to exhibit stereospecific pharmacological activities. For example, 20(S)-/20(R)-Rh 2 , the metabolites of 20(S)-/20(R)-Rg 3 , have also been studied on the stereospecific effects in their antitumor, anti-photoaging, anti-inflammatory, antioxidative, matrix metalloproteinase inhibitory and osteoclastgenesis inhibitory effects ( Liu J. et al, 2009 ; Choi et al, 2013 ; Fatmawati et al, 2014 ; Oh et al, 2014 ). Compared with 20(R)-Rh 2 , 20(S)-Rh 2 exhibits stronger anticancer effects on prostate cancer cells and human lung adenocarcinoma A549 cells ( Liu et al, 2010a ; Zhang et al, 2011 ).…”
Section: Pharmacologymentioning
confidence: 99%
“…Except for ginsenoside Rg 3 , other stereoisomeric saponins have also been found to exhibit stereospecific pharmacological activities. For example, 20(S)-/20(R)-Rh 2 , the metabolites of 20(S)-/20(R)-Rg 3 , have also been studied on the stereospecific effects in their antitumor, anti-photoaging, anti-inflammatory, antioxidative, matrix metalloproteinase inhibitory and osteoclastgenesis inhibitory effects ( Liu J. et al, 2009 ; Choi et al, 2013 ; Fatmawati et al, 2014 ; Oh et al, 2014 ). Compared with 20(R)-Rh 2 , 20(S)-Rh 2 exhibits stronger anticancer effects on prostate cancer cells and human lung adenocarcinoma A549 cells ( Liu et al, 2010a ; Zhang et al, 2011 ).…”
Section: Pharmacologymentioning
confidence: 99%
“…We observed that the average relative abundance of ginsenoside Rh 2 was higher in feces samples (0.903 × 10 6 ± 0.186 × 10 6 ) compared to that in plasma (0.378 × 10 4 ± 0.078 × 10 4 ). In the feces samples, both two stereoisomeric forms of Rh 2 were observed as 20 S - and 20 R -, and these isomers may have different pharmacological effects (Zhang et al , 2012; Chio et al , 2013). Similar to compound K, we observed that average Rh 2 amount from feces is higher in subjects consuming Western diet (1.525 × 10 6 ± 0.216 × 10 6 ) compared to those consuming Asian diet (0.279 × 10 6 ± 0.159 × 10 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…and P. ginseng. [22,23] . Compounds 3 and 4 have two fatty acids in the molecule, whereas Compounds 1 and 2 have one fatty acid.…”
Section: Resultsmentioning
confidence: 99%